AdvenTour Travels and Tours Chalatenango - Rauda Muñoz, Marlon Edenilson; Rivera Argueta, Katherinne Lisseth (universidad de El Salvador. Facultad de Ciencias y Humanidades, 2024)
Disponible en soporte impreso